Parkinson Disease Mortality Rates in Chile [Mortalidad por Enfermedad de Parkinson en Chile] - Chana-Cuevas, P (2013)
Background: Parkinson disease (PD) is the second more common neurodegenerative disorder and determines a loss in quality of life, caregiver burden and increased mortality in those affected. Aim: To determine the rates of mortality due to Parkinson disease in Chile. Material and Methods: Data were collected from death certificates between 1997 and 2008. Mortality rates were calculated and the mortality trend was established along the study period, and analyzed by age, sex and geographic region of Chile. Results: There was a steady increase in mortality over the years, particularly since 2001 (r2 = 0.85, p < 0.01). The increase in mortality rates was 0.25 per 100.000 habitants/year (r2: 0.89, p < 0.01). Mortality was always higher in men and in those older than 80 years. The highest rate (per 100,000 habitants) in Chile was observed in the region of Valparaíso (2.4) while the lowest was in Antofagasta (0.8) (t = 3.72, p < 0.05). Conclusions: Mortality associated with PD has increased progressively, consistent with the expected increase in prevalence of the disease in the population.